Management and Staff Perception of Factors Affecting Consumer Credit Marketing Performance at PT BPD NTT - Didok, Maya Susanthy; Gana, Frans; Fanggidae, Rolland E. (International Journal of Environmental, Sustainability, and Social Science, 2026)
The purpose of this study is to: 1) Describe and analyze the perceptions of management and staff regarding service quality, marketing strategy, and human resources at PT. BPD NTT 2) Describe and analyze consumer credit marketing performance at PT. BPD NTT 3) Identify the dominant factors influencing consumer credit marketing performance based on the perceptions of management and staff at PT. BPD NTT. The results of descriptive analysis show that the description of service quality, marketing strategy and human resources at PT. Bank Pembangunan Daerah Nusa Tenggara Timur in this study has met the criteria with the category of strongly agree, and also all respondent answer data passed the validity and reliability test. The results of partial inferential analysis of service quality have a significant effect on consumer credit marketing performance, marketing strategy has a positive and significant effect on consumer credit performance, human resources have a positive and significant effect on consumer credit marketing performance. The R Square value shows that the contribution of service quality, marketing strategy, and human resources to consumer credit marketing performance is 82.5%, while the remaining 17.5% is influenced by other variables outside the model studied.